مقترح نظام اداري لقواعد اختيار اسموب التنفيذ في مشاريع قطاع التشييد في العراق (Journal of Engineering, 2008)
Among the most important problems which faced the new approach is the wide use of old approach , particularly the traditional approach ( general contractor ) and the bill of quantity contract, and this were commonly used in the course of the application of fast – track approach in spite of unfulfilling the execution requirements for the fast – track , so It became necessary to look for certain contract rules to be used as a substitute suited all conditions and cases after concluding lessons from the local experiments in rebuilding issues . This research aims at analyzing the subject of shortening time factor taking in consideration the effect all the effective factors which leads to increase the cost and time A scientific methodology was followed in both theoretical and practical phases of the study . A detailed statistical analysis of the study was incorporated using questionnaire and interview method to evaluate the effective factors directly or indirectly on fast – track approach.